Critical analysis of Timochenko's speech, peace dialogues (Quaestiones Disputatae: temas en debate, 2020)
The article presents some reflections on the theoretical-methodological perspective of the critical analysis of discourse and within this, the theory of connotation to assume from a social-critical position the different discourses issued by Timochenko during the current peace process in Colombia. In this way, it is intended to elucidate and seek that the analysts of the discourse as the society, take position in front of the discourses that surround them and thus, can discover connoted or implicit meanings in relation to purposes of persuasion, credibility, denunciation, defense, manifestation of ideologies and social positions on the armed conflict and the peace process in Colombia, taking into account linguistic and extralinguistic aspects used in the construction of reality.
Keywords: critical discourse analysis; connotation; denotation and discursive strategies